Administrative Justice in the Perspective of Islamic Legal Philosophy: A Comparative Study of Ethical Legitimacy and Bureaucratic Rationality - Surahman Surahman; Abdurrahim Abdurrahim; Widyatmi Anandy; Fathul Hamdani; Uche Nnawulezi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The debate about justice in legal systems and public administration concerns not only the normative-procedural aspects but also touches on the moral, ethical, and spiritual dimensions of government practice. In the modern context, administrative law develops based on bureaucratic rationality as formulated by Max Weber, which emphasizes procedural legality, efficiency, and institutional hierarchy as sources of legitimacy for state action. In this paradigm, administrative justice is measured through adherence to written rules, procedural clarity, and impersonal administrative accountability mechanisms. However, despite guaranteeing order and efficiency, this system is often criticized for its tendency to ignore the moral substance and human values that are at the core of justice itself. Conversely, in Islamic legal philosophy, justice holds a higher and transcendental status. Justice is not merely the result of legal procedures, but rather a manifestation of divine will ('adl) and an integral part of the objectives of Islamic law (maqāṣid al-sharī‘ah). Within this framework, bureaucratic actions—whether legislative, executive, or administrative—cannot be judged just solely because they conform to the rules, but must reflect ethical legitimacy, namely conformity to moral principles, honesty, social responsibility, and orientation toward the public good (maṣlaḥah ʿāmmah). Thus, legitimacy in Islamic law is moral-spiritual, not merely legal-formal. The gap between these two paradigms raises a fundamental question in the study of legal philosophy: is modern bureaucratic rationality capable of producing substantive justice, or does it require a deeper ethical foundation as offered by Islamic legal philosophy? In the context of public administration in Muslim countries, this question becomes increasingly relevant given the demand to integrate sharia values with the principles of efficient and transparent modern governance. Through this comparative study, the research aims to explore how Islamic legal philosophy interprets administrative justice and bureaucratic legitimacy from an ethical and theological perspective, and to identify fundamental differences between ethical legitimacy in Islamic law and bureaucratic rationality in modern administrative law. This approach is expected to provide a philosophical basis for the formation of a legal and bureaucratic system that is not only structurally rational, but also morally and spiritually just